Planning-based prediction for pedestrians - Ziebart, B.D.; Ratliff, N.; Gallagher, G.; Mertz, C.; Peterson, K.; Bagnell, J.A.; Hebert, M.; Dey, A.K.; Srinivasa, S. (2009 IEEE/RSJ International Conference on Intelligent Robots and Systems, 2009)
We present a novel approach for determining robot movements that efficiently accomplish the robot's tasks while not hindering the movements of people within the environment. Our approach models the goal-directed trajectories of pedestrians using maximum entropy inverse optimal control. The advantage of this modeling approach is the generality of its learned cost function to changes in the environment and to entirely different environments. We employ the predictions of this model of pedestrian trajectories in a novel incremental planner and quantitatively show the improvement in hindrance-sensitive robot trajectory planning provided by our approach.